DESIGN SPECIFICS OF CUTOUT ANIMATION IN THE ADOBE ANIMATE PROGRAM - Khrystyna Andriivna Petrushevska (теорія та практика дизайну)
Abstract. Cut out animation is a simple and oldest type of animation, which is inextricably linked to the Chinese shadow theater. It’s a type of stop motion animation that uses cutouts or flat pieces for characters, props, and backgrounds. Unlike other types of animation that come from stop motion and have volume like puppets, in the cutout everything is flat and gives the appearance of 2D. As in all stop motion sub-techniques, the character is animated frame by frame. Cutout animation was first used in a short film in 1906. At least that’s the first record we have. The silent film is known as Humorous Phases of Funny Faces and belongs to the British director James Stuart Blackton. With the development of computer technology, this type of animation received a new life. Despite its long history, cut out animation has not lost its relevance and is actively used in animation studios around the world. Doing it in the program is much more convenient, because all elements can be created immediately in the program without wasting extra materials, you can also import any image created in another program, or simply a scanned element created by hand from classic materials such as cardboard and paper. Adobe Animate works with a system of layers and symbols for ease of animation. Symbols can be divided into individual layers, and each symbol can contain several others. Each symbol has its own timeline. This extensive system allows you to work in detail with each individual element and with the complete object. The purpose is to investigate the historical development of cut-out animation; to identify the specific features of cut-out animation in Adobe Animate program. Methodology. The article uses traditional scientific methods of historical analysis, comparative analysis, the method of system-structural analysis. Results. The historical development of cut-out animation was studied, the specifics of modern cut-out animation in the Adobe Animate program were revealed. Scientific novelty. The principle of operation of the Adobe Animate program with cut animation is considered. Practical significance. This material can be used in the cultural and educational process in the training of graphic designers.